Livelihood risks impact livestock reduction behavior of herders: evidence from Inner Mongolia, China - Haibin Dong; Saheed Olaide Jimoh; Qishen Jiang; Sibo Liu; Yanting Yin; Xiangyang Hou (Frontiers in Sustainable Food Systems, 2023)
We analyzed the primary livelihood risks faced by livestock-herding households across six counties and three grassland types in Inner Mongolia. The major livelihood risks were natural, market, financial, and policy. These risks are influenced by changes in stocking rate (SR), which are critical for controlling livestock numbers and averting risks associated with overgrazing in natural grasslands. We propose a correction method for SR based on hay purchase from a survey of 450 herders. We compared the distribution of households’ SR after the correction and used a multiple linear regression model to empirically test the effect of livelihood risks on SR. The empirical model passed robustness test and the regression results of variables were robust. SR declined across grassland types after hay purchases. The SR of the meadow steppe was reduced by 35%, typical steppe by 23%, and desert steppe by 32%. Various factors affected changes in SR, including ecological subsidies to household income, timely access to market information, and annual livestock losses. We discuss implications of our findings for policy, market transactions, livestock insurance, social security, and formal credit systems in pastoral areas.